KORELASI ANTARA DERAJAT PENYAKIT SIROSIS HATI BERDASARKAN KLASIFIKASI CHILD-TURCOTTE-PUGH DENGAN KONSENTRASI TROMBOPOIETIN SERUM - Juliana, I Made; Wibawa, I Dewa Nyoman (journal of internal medicine, 2008)
Thrombocytopenia is one of the most frequent haematological abnormalities in patients with livercirrhosis. It is generally considered to be due to pooling and destruction of the platelets in enlarged spleenwhich was defined as hypersplenism. Portal decompression procedures, either by surgical shunts ortransjugular intrahepatic portosystemic shunt (TIPS) have not led to a consistent rise in thrombocytes count.With the discovery of the lineage specific cytokine thrombopoietin (TPO) in 1994, the missing link betweenhepatocelular function and thrombopoiesis was found. TPO is predominantly produced by the liver andconstitutively expressed by the hepatocytes. In liver cirrhosis, the damaged of liver cells reduced TPOproduction. This leads to reduce thrombopoiesis in the bone marrow and consquently causesthrombocytopenia. However, these two pathogeneses were still remained controversial results in previousstudy abroad.The aim of this study was to determine the correlation between disease severity of liver cirrhosisbased on Child-Turcotte-Pugh classification and serum thrombopoietin concentration. An analytic crosssectional study had been conducted among liver cirrhotic patients in Sanglah Hospital Denpasar. The subjectwere adult liver cirrhotic patients that were not on upper or lower gastro-intestinal tract bleeding, septiccodition/septic shock, without history of taking antithrombocytic drugs or received platelets transfusion inlast two weeks, and no history of thrombocytopenia due to primary haematologic disorders. Statisticalanalysis was done by Spearman’s test and multivariate linier regression model, with significant level p <0,05.The number of subjects were 39 liver cirrhotic patients consist of 28 (71.8%) men and 11 (28.2%)women. The median of age was 53 (25 – 68) years. We found subjetcs with Child-Turcotte-Pugh class A 3(7.7%), B 18 (46.2%) and C 18 (46.2%) respectively with the median of Child-Turcotte-Pugh score was 9 (6– 14). The range of serum TPO concentration was 1.10 – 224.60 pg/ml, median of serum TPO was 40.60pg/ml. The median of thrombocyte was 103 x 103/L with range of 30 – 729 x 103/L. Liver cirrhoticpatients with thrombocytopenia were 29 (74.4%), 41.0% of them with moderate thromboytopenia. We foundnegative correlation between Child-Turcotte-Pugh score and serum TPO concentration ( r = - 0.319; p = 0.048) but there was no correlation between Child-Turcotte-Pugh class and TPO concentration. (r = -0.303;p = 0.061). We found significant positif correlation between thrombocyte count and serum TPOconcentration also (r = 0.354; p = 0.027). Based on multivariate linier regression model, we did not findsignificant association between TPO concentration and Child-Turcotte-Pugh score (p = 0.153) orthrombocyte count (p = 0.208), respectively. Conclusion: there was no correlation between disease severityof liver cirrhosis based on Child-Turcotte-Pugh classification and serum thrombopoietin concentration.